Gonadotropin releasing hormone receptor ligand interactions - Flanagan, Colleen A (Division of Chemical Pathology, 2018)
The decapeptide, gonadotropin releasing hormone (GnRH), is the central regulator of reproductive function. It binds to receptors on the gonadotrope cells of the pituitary and stimulates release of luteinizing hormone (LH) and follicle stimulating hormone (FSH). Eleven different structural forms of GnRH have now been identified in various animal species. Chimaeric analogues of some of the variant forms of GnRH were synthesized in order to study the functional significance of the most common amino acid substitutions, which occur in positions 5, 7 and 8. Peptide binding affinities for sheep and rat GnRH receptors and potencies in stimulating LH and FSH release from cultured sheep pituitary cells and LH release from cultured chicken pituitary cells were measured. Histidine in position 5 decreased LH releasing potency in chicken cells, but slightly increased receptor binding affinity in rat and sheep membranes. Tryptophan in position 7 had minimal effect on GnRH activity in mammals, but increased LH release in chicken cells. Although differences in the structural requirements of mammalian and chicken GnRH receptors were anticipated, it was also found that rat GnRH receptors exhibited higher affinity for analogues with Tryptophan in position 7, than did sheep GnRH receptors. Substitutions in position 8 revealed the most marked differences in the structural requirements of mammalian and chicken GnRH receptors. Arginine was required for high GnRH activity in mammalian systems, but analogues with neutral substitutions in position 8 were more potent in chicken pituitary cells. The tolerance of position 8 substitutions, combined with the relatively small effects, in chicken cells, of incorporating a D-amino acid in position 6, indicate that the chicken GnRH receptor is less stringent than mammalian receptors in its recognition of peptide conformation. To examine how changes in ligand structure cause changes in receptor binding affinity and receptor activation, it was necessary to know the structures of the GnRH receptors. A protocol was developed for the purification of GnRH binding proteins from detergent-solubilized pituitary membranes, by affinity chromatography. This procedure yielded a protein which migrated as a single band on sodium dodecyl sulfate polyacrylamide gel electrophoresis, but was different from the recently cloned GnRH receptor. To test the proposal that the arginine residue in mammalian GnRH interacts with an acidic receptor residue, eight conserved acidic residues of the cloned mouse GnRH receptor were mutated to asparagine or glutamine. Mutant receptors were transiently expressed in COS-1 cells and tested for decreased preference for Arg⁸-containing ligands by ligand binding and inositol phosphate production. One mutant receptor, in which the glutamate residue in position 301 was mutated, exhibited decreased affinity for mammalian GnRH. The mutant receptor also exhibited decreased affinity for [Lys⁸]-GnRH, but unchanged affinity for [Gln⁸]-GnRH compared with the wildtype receptor, and increased affinity for the acidic analogue, [Glu⁸]-GnRH. This loss of affinity was specific for the residue in position 8, because the mutant receptor retained hiszh affinity for analogues with favourable substitutions in positions 5, 6 and 7. Thus, the Glu³⁰¹ residue of the GnRH receptor plays a role in receptor recognition of Arg⁸ in the ligand, consistent with an electrostatic interaction between these two residues. The Glu³⁰¹ and Arg⁸ residues were not required for the high affinity interactions of conformationally constrained peptides. This indicates that an interaction which involves these two residues may induce changes in the conformation of GnRH after it has bound to the receptor.